Pendekatan Restorative Justice Terhadap Tindak Pidana Pencurian Oleh Pelaku Dibawah Umur - Luftia Gunawan; Dian Ekawaty Ismail; Suwitno Yutye Imran (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This research is intended to: (1) find out how restorative justice is implemented by investigators in handling criminal acts of theft committed by children (2) to find out what factors hinder the application of restorative justice in handling criminal acts of theft committed by children. This research uses a type of normative legal research, with a statutory approach and a case approach. The sources of legal materials used are primary legal materials and secondary legal materials. The results of the research show, first, the application of restorative justice to criminal acts of theft handled by investigators at the Gorontalo Police is carried out by carrying out mediation between the victim/victim's family and the perpetrator's child/family of the perpetrator. children, and must fulfill material requirements such as not causing unrest, not being a serious crime, and there being compensation to the victim by the child perpetrator, and must fulfill formal requirements. Second, the factors that hinder the application of restorative justice to criminal acts of theft committed by children handled by Gorontalo City Police investigators consist of the failure to fulfill the peace agreement between the parties (victim and perpetrator), and no compensation to the victim, making the legal process impossible. can be implemented with restorative justice.